Management of Severe COVID-19 in Pregnancy - Yassamine Abourida; Houssam Rebahi; Imane Oussayeh; Hajar Chichou; Bouchra Fakhir; Abderraouf Soummani; Hicham Jalal; Fatiha Bennaoui; Nadia El Idrissi Slitine; Fadl Mrabih Rabou Maoulainine; Ahmed Rhassane El Adib; Mohamed Abdenacer Samkaoui (Case Reports in Obstetrics and Gynecology)
The scarcity of data concerning pregnant patients gravely infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) makes their management difficult, as most of the reported cases in the literature present mild pneumonia symptoms. The core problem is laying out evidence on coronavirus’s implications on pregnancy and delivery, as well as vertical transmission and neonatal mortality. A healthy 30-year-old pregnant woman, gravida 6, para 4, at 31 weeks of gestation, presented severe pneumonia symptoms promptly complicated with premature rupture of membranes (PROM). A nasopharyngeal swab returned positive for SARS-CoV-2 using reverse transcription polymerase chain reactions (RT-PCR). The parturient underwent a cesarean delivery. This paper is an attempt to outline management of the critical condition of COVID-19 during pregnancy.